ANALYSIS STRATEGY OF HUMAN RESOURCES DEVELOPMENT PT KREASI CIPTA UTAMA - Aprinda KOMELIANTARI (Journal of Education and Leadership in Education, 2020)
This research aims to reveal the strategy of human resources development of PT Kreasi Cipta Utama. The methods used is qualitative descriptive method by obtaining data naturally, it covers data collection through observation, structured interviews and document analysis. The research concluded the strategy of human resources development can be revealed based on two dimensions: education and training. Company is expected to be able to prepare education participant through informal development and formal development so employees can meet the qualification of education participant. Education participant that met qualification will help education program that company runs to be in line with the objective so it can contribute to company performance.